Kromogranin A in njegova klinična uporabnost - Pavlin, Rudolf (Zdravniški vestnik, 2003)
Background. An old widely recepted opinion was that the medullary part of the suprarenal gland was primarily responsible for a adequate response to stress. Recently a broader significance of the gland has been recognised. The chromogranin A which is produced and secreted by its enterochromaffine cells is extensively involved in several physiological and pathological processes inthe body. Determination of the serum concentration of chromogranin A is nowadays extremely usefulfor diagnosis of the neuroendocrine tumors of the gastrointestinal tract. Conclusions. In the present article its localisation in the body and its biochemistry are described, as well as normal serum concentration values and their changes in various pathological states.
Keywords: Adrenal Gland Neoplasms; biokemija; Biosynthesis; Blood; Carcinoid Tumor; Chromogranins; Diagnostic Use; diagnostika; Feokromocitom; Hipertenzija; Hypertension; Karcinoidni tumor; Kidney Failure; kromogranin A; Kromogranini; Ledvična odpoved; Nadledvična žleza, novotvorbe; Neuroendocrine Tumors; Nevroendokrini tumorji; Pheochromocytoma; Prostata, novotvorbe; Prostatic Neoplasms; Stomach Neoplasms; tumorji; Želodec, novotvorbe